Design of telecommunications regulatory authorities in fragile states: The case of Palestine - Omar Dhaher (International Telecommunications Society (ITS), 2012)
This paper discusses regulatory design in unstable states. It focuses on the regulatory attributes of the regulatory authority. The paper analyzes three unstable states (Kosovo, Lebanon and Palestine) and offers a set of policy recommendations for additional and essential safeguards that shall produce and maintain an effective authority.
Keywords: L96; Z00; 330; Telecommunications regulation; Regulatory design; Institutional Reform